1981
DOI: 10.1002/pen.760210105
|View full text |Cite
|
Sign up to set email alerts
|

Bending and breaking fibers in sheared suspensions

Abstract: An experimental study was made of single fibers rotating and bending in Couette flow of a Newtonian liquid. A previous result for critical fib,er buckling was retested and found satisfactory, and the traqsition between 'springy' and 'snake' rotation was delineated. The minimum radius of curvature achieved during rotation in the "snake orbit" regime was measured as a function of fiber aspect ratio, Young's modulus, and fluid shear stress. Two correlations are presented which are constrained to satisfy limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…19 Reasonable agreement was found with experimental data, 19 when the radius of curvature was greater than 30 fiber diameters, for the particular type of fiber used in the experiments. 19 Reasonable agreement was found with experimental data, 19 when the radius of curvature was greater than 30 fiber diameters, for the particular type of fiber used in the experiments.…”
Section: Discussionmentioning
confidence: 56%
“…19 Reasonable agreement was found with experimental data, 19 when the radius of curvature was greater than 30 fiber diameters, for the particular type of fiber used in the experiments. 19 Reasonable agreement was found with experimental data, 19 when the radius of curvature was greater than 30 fiber diameters, for the particular type of fiber used in the experiments.…”
Section: Discussionmentioning
confidence: 56%
“…doi:10.1016/j.jnnfm.2004.09.004 limit in a shear flow to break a fiber. Salinas and Pittman [7] have validated the criterion proposed by Forgacs and Mason. They have shown that longer fibers are more easily broken in a simple shear flow.…”
Section: Introductionmentioning
confidence: 83%
“…So that the force of glass fiber underwent during the process of LFT-PP extrusion would be about 10M Pa, as shown by Equation (11): (11) Salinas et al posted essential condition presented by Equation (12) that fiber would fracture during the compounding [17]. As for glass fiber, = 10 6 MPa.…”
Section: Influence Of Shear Forcementioning
confidence: 99%